2014
DOI: 10.1021/jp5002435
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study of Ultrafast Excited-State Proton Transfer in Water and D2O Providing the Missing RO···H+ Ion-Pair Fingerprint

Abstract: Steady-state and time-resolved optical techniques were employed to study the photoprotolytic mechanism of a general photoacid. Previously, a general scheme was suggested that includes an intermediate product that, up until now, had not been clearly observed experimentally. For our study, we used quinone cyanine 7 (QCy7) and QCy9, the strongest photoacids synthesized so far, to look for the missing intermediate product of an excited-state proton transfer to the solvent. Low-temperature steady-state emission spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“… 7 , 8 , 18 – 21 Previous results showed multi-stage proton transfer processes involving the formation and separation of the charge-separated contact ion pair on the ps timescale. 19 , 20 , 22 25 In contrast to direct proton transfer from HPTS to carboxylate ions which can occur within ∼200 femtoseconds (fs) at high base concentrations, 8 , 23 , 26 pure water provides a general environment with moderate H-bonding strength that can elucidate aqueous proton transfer pathways with different number of intervening water molecules, 19 , 21 , 27 revealing characteristic time constants of ∼3 and 90 ps in the commonly reported kinetic scheme for ESPT. Based on femtosecond transient absorption results, we select a strategic Raman pump wavelength at 580 nm that pre-resonantly enhances both the photoexcited protonated and deprotonated chromophore through the entire time window, directly tracking molecular structural evolution of the photoacid along multiple atomic motion trajectories.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 18 – 21 Previous results showed multi-stage proton transfer processes involving the formation and separation of the charge-separated contact ion pair on the ps timescale. 19 , 20 , 22 25 In contrast to direct proton transfer from HPTS to carboxylate ions which can occur within ∼200 femtoseconds (fs) at high base concentrations, 8 , 23 , 26 pure water provides a general environment with moderate H-bonding strength that can elucidate aqueous proton transfer pathways with different number of intervening water molecules, 19 , 21 , 27 revealing characteristic time constants of ∼3 and 90 ps in the commonly reported kinetic scheme for ESPT. Based on femtosecond transient absorption results, we select a strategic Raman pump wavelength at 580 nm that pre-resonantly enhances both the photoexcited protonated and deprotonated chromophore through the entire time window, directly tracking molecular structural evolution of the photoacid along multiple atomic motion trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] However, examples of a clear identication of the CIP* spectral signatures are scarce. [23][24][25][26][27][28] Few studies reported an intermediate uorescence between the ROH* and RO À * bands that was attributed to the contact ion pairs but this was observed only in supercritical, 23 frozen or strongly acidic aqueous solutions 24,25 and aprotic organic solvents. 26,27 Therefore, it remains unclear whether the CIP* emission would be detectable in protic solvents at a moderate pH range.…”
Section: Introductionmentioning
confidence: 99%
“…In water, HPTS dynamics is highly nonexponential having contributions from at least three different time constants: <1, ∼3, and ∼90 ps. 48 …”
Section: Resultsmentioning
confidence: 99%